Występowanie i nasilenie zaburzeń lękowych i depresyjnych u kobiet z rakiem piersi przygotowywanych do leczenia chirurgicznego = Incidence and intensification of anxiety and depressive disorders at women with breast cancer prepared for the surgical treatm - Marta Łuczyk; Agata Pietraszek; Robert Łuczyk; Andrzej Stanisławek; Zdzisława Szadowska-Szlachetka; Marianna Charzyńska-Gula (Kazimierz Wielki University, 2015)
Łuczyk Marta, Pietraszek Agata, Łuczyk Robert, Stanisławek Andrzej, Szadowska-Szlachetka Zdzisława, Charzyńska‑Gula Marianna. Występowanie i nasilenie zaburzeń lękowych i depresyjnych u kobiet z rakiem piersi przygotowywanych do leczenia chirurgicznego = Incidence and intensification of anxiety and depressive disorders at women with breast cancer prepared for the surgical treatment. Journal of Education, Health and Sport. 2015;5(5):52-66. ISSN 2391-8306. DOI: 10.5281/zenodo.17395 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A52-66 https://pbn.nauka.gov.pl/works/557638 http://dx.doi.org/10.5281/zenodo.17395 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 15.04.2015.   Występowanie i nasilenie zaburzeń lękowych i depresyjnych u kobiet z rakiem piersi przygotowywanych do leczenia chirurgicznego Incidence and intensification of anxiety and depressive disorders at women with breast cancer prepared for the surgical treatment   Marta Łuczyk1, Agata Pietraszek1, Robert Łuczyk2, Andrzej Stanisławek1, Zdzisława Szadowska-Szlachetka1, Marianna Charzyńska-Gula1 1 Zakład Onkologii Katedra Onkologii i Środowiskowej Opieki Zdrowotnej Wydział Nauk o Zdrowiu Uniwersytet Medyczny w Lublinie 1 Oncology Department, Chair of Oncology and the Environmental Health Care, Department of Health Sciences, Medical University of Lublin 2 Katedra Interny z Zakładem Pielęgniarstwa Internistycznego Wydział Nauk o Zdrowiu Uniwersytet Medyczny w Lublinie 2 Department of the Internal Medicine with the Unit of Internal Nursing, Department of Health Sciences, Medical University of Lublin   Streszczenie Wstęp. Rozpoznanie choroby nowotworowej piersi wywiera szczególny wpływ na stan psychiczny kobiety. Jedną z negatywnych reakcji emocjonalnych u kobiet po rozpoznaniu choroby nowotworowej są zaburzenia lękowe, którym mogą towarzyszy zaburzenia depresyjne. Cel pracy. Ocena występowania i nasilenia zaburzeń lękowych i depresyjnych wśród kobiet z rakiem piersi oczekujących na zabieg operacyjny. Materiał i metoda. Badania przeprowadzono metodą sondażu diagnostycznego, techniką ankiety z użyciem narzędzi: Szpitalnej Skali Oceny Lęku i Depresji (HADS), Skali wizualno - analogowej zaadoptowanej do oceny lęku, autorskiego kwestionariusza wywiadu. Do badań zakwalifikowano 150 kobiet z rakiem piersi. Wyniki. W grupie chorych z rakiem piersi przygotowywanych do leczenia chirurgicznego u 93 (62,00%) osób wystąpiły zaburzenia lękowe, u 24 (19,33%) chorych stwierdzono stany graniczne, u 28 kobiet (18,67%) nie stwierdzono zaburzeń. Ponad 95% kobiet odczuwało niepokój przed chorobą nowotworową, a 89% badanych deklarowało odczuwanie lęku przed leczeniem chirurgicznym. Stwierdzono występowanie zaburzeń depresyjnych u 24 osób (16,00%), a u 39 (26,00%) osób stwierdzono stany graniczne. U 58% (87,00%) badanych kobiet nie stwierdzono zaburzeń. Wnioski. U badanych kobiet stwierdzono występowanie zaburzeń lękowych, natomiast w mniejszym stopniu zaobserwowano zaburzenia depresyjne. Prowadzenie badań oceniających występowanie lęku w okresie przedoperacyjnym powinno stać się rutynowym postępowaniem w przygotowaniu chorych do zbiegu operacyjnego. Słowa kluczowe: fobie, zaburzenia lękowe, zaburzenia depresyjne, nowotwory sutka.   Abstract Introduction. Diagnosing cancer of the breast exerts special impact on the mental state of the woman. One of negative emotional reactions at women after diagnosing cancer are anxiety disorders, possibly accompanied by depressive disorders. The aim of the study. Evaluation of appearing and increasing anxiety disorders and depressive amongst women with breast cancer waiting for the operation treatment. Materials and methods. The research was conducted using method of the diagnostic survey, technique of the questionnaire form using the following tools: Hospital Scale of Evaluation of Fear and Depression (HADS), Visual - Analogue Scale adopted for the evaluation of fear, of author's own questionnaire. The study encompassed 150 women with breast cancer. Results. In the group of patients with breast cancer prepared for the surgical treatment, at 93 (62.00%) of individuals, there appeared anxiety disorders, at 24 (19.33%) of patients were border states were diagnosed, at 28 women (18.67%) disorders weren't stated. Over 95% of women felt anxious as for their cancer, and 89% of the examined declared feeling anxious before the surgical treatment. Appearing of depressive disorders was stated at 24 individuals (16.00%), and at 39 (26.00%) patients there were stated border states. At 58% (87.00%) of the examined women no disorders were  stated. Conclusions. At examined women appearing of anxiety disorders was stated, however to a lesser degree depressive disorders were observed. Judging the conduct of research appearing of fear in the preoperative period should become routine proceedings in preparation of sick individuals for the operating concurrence. Key words: phobic disorders, anxiety disorder, depressive disorder, breast neoplasms.